Pengaruh Perjanjian Pranikah Terhadap Perlindungan Aset Perkawinan Pada Generasi Z Dalam Kerangka Undang-Undang Perkawinan Dan Putusan Mahkamah Konstitusi Nomor 69/PUU-XIII/2015 - jesslyn, chlaresta; Sudharma, Kadek Januarsa Adi (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
This study analyzes the effect of prenuptial agreements on the protection of marital assets among Generation Z within the framework of the Marriage Law and the implications of Constitutional Court Decision No. 69/PUU-XIII/2015. Normatively, the joint property regime poses the risk of asset commingling and debt liability; prenuptial agreements/separate property become mitigation instruments. The Constitutional Court ruling expands the scope of protection by recognizing marriage agreements that can be made and/or ratified after marriage (post-nuptial), thus providing flexibility for young couples. The method used is normative legal research (analysis of legislation, jurisprudence, and doctrine) enriched by limited empirical findings on Generation Z preferences (legal literacy, attitudes towards personal finance, and risk tolerance). The results show that prenuptial agreements are effective in separating ownership, reducing potential disputes, and protecting pre-marital assets, inheritance, and the business results of each party; while the post-nuptial scheme following the Constitutional Court's decision functions as a “remedial tool” when an agreement is not made before the marriage contract. The main obstacles include social stigma, low contractual literacy, and access to notary services. The study recommends improving Gen Z-friendly legal education, adaptive standard clause models (including debt and digital asset management), and simpler registration procedures to ensure legal certainty.